Iridium‐Catalyzed Enantioselective Allylic Alkylation with Functionalized Organozinc Bromides1. Issue 26 (12th May 2015) - Hamilton, James Y.; Sarlah, David; Carreira, Erick M.
Abstract Iridium‐catalyzed enantioselective allylic alkylation of branched racemic carbonates with functionalized alkylzinc bromide reagents is described. Enabled by a chiral Ir/(P, olefin) complex, the method described allows allylic substitution with various primary and secondary alkyl nucleophiles with excellent regio‐ and enantioselectivities. The developed reaction was showcased in a concise, asymmetric synthesis of (−)‐preclamol.